Description of The Public Knowledge and Stigma Against PLWHA in Niki-Niki Sub district, Central Amanuban District, TTS Regency - WINDA YULIANA KURNIAWATI ASAR; Imelda F. E. Manurung; Mustakim Sahdan (Journal of Health and Behavioral Science, 2021)
The stigma against People Living With HIV and AIDS (PLWHA) is influenced by several factors, including low levels of formal education and lack of knowledge related to to HIV and AIDS. The aim of this study was to describe the knowledge and stigma of the community towards PLWHA in Niki-Niki Village, Central Amanuban District, TTS Regency. This study uses descriptive quantitative research methods with Simple Random Sampling techniques to 70 people. The research instrument used was a questionnaire and the analysis was carried out quantitatively descriptive. The results showed that respondents with good knowledge had higher stigma against PLWHA than those with less knowledge. Many people do not really understand about the transmission of the HIV. Hopefully the public will increase their knowledge about HIV, specifically HIV transmission, and eliminate the stigma of PLWHA.